PERBANDINGAN PEMBERHENTIAN PRESIDEN DALAM MASA JABATAN DI INDONESIA DAN AMERIKA SERIKAT - Fenti Ermatika. EE; Mexsasai Indra; Junaidi ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
The president is head of state in a presidential system of government. The post of president as head of state is very important, it is not impossible that the president did the wrong action of the constitution and the rule of law to the detriment of the people and country. The constitution governing the restrictions on the actions the president to hold these constitutions.dismissalm of the president of a country as a means of power control. Therefore the necessary comparison with the same system of government with other countries more have the same application in the dismissal of the president. Problems associated with it, the author became interested in better compared associated with the termination of the tenure of the president between Indonesia and the United States. Through this research can be found in the process of laying the presidential term of office in Indonesia and the United States, as well as the similarities and differences can be found, as well as the strengths and weaknesses of the application of the system in both countries.Keyword : Dismissal of the President – Length of Service – UUD 1945 -Constitution